Le role du lait dans le systeme pastoral du Sud Darfur - Kerven, C. (1987)
Describes the characteristics of dairy production and processing in South Darfur and provides an analysis of the way in which pastoral families vary their diets according to seasonal food shortages and shifting terms of trade between milk and food grains.